Production Performance of Four Pig Herds Infected With Porcine Reproductive and Respiratory Syndrome Using the “Load-Close-Exposure” Approach in China - Zhang, Zhendong; Qu, Xiangyang; Wang, Xiaoquan; Li, Zhi; Yang, Shuqing; Sun, Liumei; Zhou, Bin (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most important swine diseases causing enormous losses to pig producers all over the world. The intervention measure of “load-close-exposure” [interrupting the introduction of replacement pigs combined with whole-herd exposure to live PRRS virus (PRRSV)] has been widely used in North America and has shown wonderful outcomes in controlling PRRS in the field. In the present study, we performed analyses of the production performance of four herds acutely infected with PRRSV by adopting this measure for the first time in China. Our results showed that the development rate of gilts decreased by a mean of 8.56%, the farrowing rate of breeding sows decreased from 86.18 to 77.61%, the number of piglets born alive per sow decreased by a mean of 0.73 pigs, and the pre-weaning and post-weaning mortality of piglets increased by a mean of 2.74–4.97% compared to the parameters of 6 months before an outbreak. The time to PRRSV stability (TTS), defined as the time in weeks it took to produce PRRSV-negative pigs at weaning, is an important indicator of successful control of PRRSV. The median TTS among herds A, C, and D was 21.8 weeks (21.6 22.1 weeks). In herd B, TTS was 42.3 weeks, which could be explained by the double introduction of gilts. Our study suggests that the “load-close-exposure” strategy may be a good alternative for Chinese producers and veterinaries to control PRRS in the field.